PENGEMBANGAN ALAT UKUR KEPUASAN TERHADAP KUALITAS LAYANAN JASA ATKP MEDAN - Hutabarat, Liber Tommy; Novalina, Susi Diriyanti; Sinaga, Yustian (Psychology Department Faculty of Psychology Universitas Medan Area, 2016)
The purpose of this study was to develop a measurement tool which is useful for an evaluation of customer satisfaction with the quality of service ATKP Medan North Sumatera covering Dormitory, Library, Psychology, Polyclinic, Parenting, Education and Laboratorium.Peneliti will take measurements of customer satisfaction based on the aspects of satisfaction expressed by Wilkie consisting of five elements of expectations, performance, comparison, confirmation or disconfirmation, and discrepancy. Stages of analysis item satisfaction scale of services being developed include: (1) analysis of content validity, (2) test the validity, (3) the reliability test, (4) calculate the scale of five categories based on the mean and standard deviation to determine the category of the level of satisfaction service. In the pilot scale using a sample measuring 97 Midshipman ATKP Medan with random side technique. The data obtained will be analyzed using Cronbach alpha reliability analysis to look at the scale reliability and item-total correlation analysis (rix) to see the different power test item once the validity of the content. Based on the analysis of reliability and validity of the obtained results of user satisfaction scale reliability dormitory unit, Clinic, Library, Parenting, Education, Psychology and laboratories greater than 0.9 with rix value greater than 0.3. This value indicates that the scale of satisfaction of services that have been prepared to have the precision and accuracy of a measuring instrument and be able to demonstrate the reliability or reliable.